2022 Kansas Fertilizer Research Report (Kansas Agricultural Experiment Station Research Reports, 2022)
A summary of research conducted in 2018-2021 on fertilizer use and management practices for crops in Kansas. Published in 2022 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Service https://www.ag.k-state.edu/.
Keywords: phosphorus; soil test; tissue analysis; corn; early season; phosphorus uptake; genotype; nitrogen rate; precipitation; Triticum aestivum L.; winter wheat; nitrogen stabilizer; nitrogen timing; nitrogen source; 4R; zinc; copper; Mehlich-3; DTPA; micronutrients; soil pH; Kansas State experiment field; 2021 growing season weather; Kansas weather; fertilizer research; nitrogen; potassium; tall fescue; endophyte-free